Spatial patterning of scent in petunia corolla is discriminated by bees and involves the ABCG1 transporter. (30th April 2021) - Skaliter, Oded; Kitsberg, Yaarit; Sharon, Elad; Shklarman, Elena; Shor, Ekaterina; Masci, Tania; Yue, Yuling; Arien, Yael; Tabach, Yuval; Shafir, Sharoni; Vainstein, Alexander
SUMMARY: Floral guides are patterned cues that direct the pollinator to the plant reproductive organs. The spatial distribution of showy visual and olfactory traits allows efficient plant–pollinator interactions. Data on the mechanisms underlying floral volatile patterns or their interactions with pollinators are lacking. Here we characterize the spatial emission patterns of volatiles from the corolla of the model plant Petunia  ×  hybrida and reveal the ability of honeybees to distinguish these patterns. Along the adaxial epidermis, in correlation with cell density, the petal base adjacent to reproductive organs emitted significantly higher levels of volatiles than the distal petal rim. Volatile emission could also be differentiated between the two epidermal surfaces: emission from the adaxial side was significantly higher than that from the abaxial side. Similar emission patterns were also observed in other petunias, Dianthus caryophyllus (carnation) and Argyranthemum frutescens (Marguerite daisy). Analyses of transcripts involved in volatile production/emission revealed lower levels of the plasma‐membrane transporter ABCG1 in the abaxial versus adaxial epidermis. Transient overexpression of ABCG1 enhanced emission from the abaxial epidermis to the level of the adaxial epidermis, suggesting its involvement in spatial emission patterns in the epidermal layers. Proboscis extension response experiments showed that differences in emission levels along the adaxial epidermis, that is, petal base versus rim, detected by GC‐MS are also discernible by honeybees. Significance Statement: Flowers generate an array of special metabolites involved in numerous processes in the plant life cycle. Here, we reveal spatial emission patterns of phenylpropanoid/benzenoid volatiles in corollas of the model plant petunia. Along the adaxial epidermis, emission was correlated with cell density; however, between the adaxial and abaxial epidermal layers, emission patterns are suggested to result from differences in expression levels of the transporter ABCG1 .